2010
DOI: 10.1177/1099800410365368
|View full text |Cite
|
Sign up to set email alerts
|

Adipokine Concentrations in Nonobese Women: A Study of Reproductive Aging, Body Mass Index, and Menstrual Cycle Effects

Abstract: Objective To explore the influence of reproductive aging, body mass index (BMI) and the menstrual cycle on adiponectin (AD) and leptin concentrations. Design Cross-sectional comparison in age- and BMI-matched non-obese volunteers with regular cycles (CO, n = 19) or in early menopause (EPM, n = 19), aged 40–52 years, and a young cycling group (CY, n = 21), aged 20–30 years. Measures: sex steroids, fasting AD, leptin, insulin, glucose, adiponectin/leptin (A/L) ratio and HOMA-IR. In ovulatory women, AD, estradi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 43 publications
(79 reference statements)
2
11
0
Order By: Relevance
“…The mean 25(OH)D level was 24.4 ± 9.4 ng/ml in women from NHS and 28.7 ± 9.9 ng/ml in men from HPFS, consistent with vitamin D insufficiency in both cohorts by current clinical convention (3). As expected, women had higher adiponectin concentrations than men (17.9 ± 7.7 vs. 10.0 ± 8.1 µg/ ml) (11), and postmenopausal women had higher adiponectin levels than premenopausal women (18.3 ± 7.7 vs. 15.7 ± 7.0 µg/ ml) (18). Both study populations exhibited expected trends in demographic, physical, and dietary characteristics when stratified by BMI categories (Tables 1 and 2).…”
Section: Population Characteristicssupporting
confidence: 77%
See 2 more Smart Citations
“…The mean 25(OH)D level was 24.4 ± 9.4 ng/ml in women from NHS and 28.7 ± 9.9 ng/ml in men from HPFS, consistent with vitamin D insufficiency in both cohorts by current clinical convention (3). As expected, women had higher adiponectin concentrations than men (17.9 ± 7.7 vs. 10.0 ± 8.1 µg/ ml) (11), and postmenopausal women had higher adiponectin levels than premenopausal women (18.3 ± 7.7 vs. 15.7 ± 7.0 µg/ ml) (18). Both study populations exhibited expected trends in demographic, physical, and dietary characteristics when stratified by BMI categories (Tables 1 and 2).…”
Section: Population Characteristicssupporting
confidence: 77%
“…Prudent dietary pattern scores were derived from semi‐quantitative food frequency questionnaires as previously described (23). In women from NHS, we also adjusted for menopausal status (18). Dietary calcium and potassium intake included that from food sources as well as supplements.…”
Section: Methods and Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, serum adiponectin levels were significantly decreased, whereas serum leptin levels were increased in obese postmenopausal women compared to normoweight women (57). Adiponectin concentration appears to be higher in normoweight than in overweight women in early postmenopause (52). Taken together, these data support the idea of an inhibitory role for both estrogen and body fat composition in the secretion of this adipokine.…”
Section: Adulthood and Postmenopausesupporting
confidence: 76%
“…In addition, no significant changes in serum adiponectin concentrations were reported by Kleiblova et al (51) in relation to sex hormones or to the degree of insulin sensitivity during the menstrual cycle. In this regard, Rouen et al (52) observed no variation in adiponectin secretion during the menstrual cycle. These findings suggest that adiponectin is probably not related to reproductive functions in adult women.…”
Section: Adulthood and Postmenopausementioning
confidence: 98%